Team- and Problem-Based Learning in Health Services: A Systematic Literature Review of Recent Initiatives in the United States - Eileen S. Alexander; Ashley A. White; Ashley Varol; Kacey Appel; Cristian Lieneck (MDPI AG, 2024)
The COVID-19 pandemic caused a sudden shift to virtual platforms. Physical distance and limited experience with both synchronous and asynchronous teamwork at work and school hampered problem-solving and the development of critical thinking skills. Under these circumstances, the implementation of team-based and problem-based learning (TBL, PBL, respectively) required a reevaluation of how teams collaborate and engage in problem-solving remotely. The research team conducted a systematic review to identify health services studies, themes, and attributes of learning initiatives associated with the success of TBL and PBL conducted during the COVID-19 pandemic. This systematic review was conducted using the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines. The review results identified three themes associated with TBL and PBL learning initiatives in health services: (1) TBL and PBL have transformed health services education with modified TBL (mTBL) and modified PBL (mPBL) as the new norms; (2) the amplification of age-appropriate principles for professional motivation in healthcare; and (3) active learning impacts practical abilities for professional success and future leadership roles. The pandemic underscored the importance of flexibility, resilience, and innovation in TBL and PBL approaches in health services education. Despite the superiority of mPBL and mTBL, the barriers to implementation and student acceptance of active learning include inadequate resource and space allocation, and student preferences for passive, traditional lecture. Further, online learning required increased facilitator training, administration time, and time to provide feedback.